2021
DOI: 10.3389/fcell.2021.743908
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Impact of Molecular Subtyping of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma is a highly lethal malignancy, which has now become the seventh most common cause of cancer death in the world, with the highest mortality rates in Europe and North America. In the past 30 years, there has been some progress in 5-year survival (rates increasing from 2.5 to 10%), but this is still extremely poor compared to all other common cancer types. Targeted therapies for advanced pancreatic cancer based on actionable mutations have been disappointing, with only 3–5% showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 89 publications
(195 reference statements)
0
41
0
1
Order By: Relevance
“…Yue et al, 2020;Dijk et al, 2020;Martens et al, 2019;Rashid et al, 2020). However, this will yield a future diagnostic tool for personalized medicine (Froeling et al, 2021;Xu et al, 2021). As an advantage of scRNAseq, tumor subtypes could be determined at the cellular resolution and revealed the presence of intra-tumoral heterogeneity.…”
Section: Two Major Caf Types and Their Interaction With Malignant Cellsmentioning
confidence: 99%
“…Yue et al, 2020;Dijk et al, 2020;Martens et al, 2019;Rashid et al, 2020). However, this will yield a future diagnostic tool for personalized medicine (Froeling et al, 2021;Xu et al, 2021). As an advantage of scRNAseq, tumor subtypes could be determined at the cellular resolution and revealed the presence of intra-tumoral heterogeneity.…”
Section: Two Major Caf Types and Their Interaction With Malignant Cellsmentioning
confidence: 99%
“…Instead, it becomes imperative to create highly personalized treatment schemes for these patients, targeted therapies homing in on the specific molecular mechanisms driving tumor progression in each case. To this end, various researchers have called for the implementation of molecular subtyping using transcriptomic techniques—scRNA-seq in particular—in clinical trials [ 72 , 73 , 74 ]. Others still recommend profiling the tumor tissue of all patients coming in with PDAC [ 75 ] with the recent National Comprehensive Cancer Network (NCCN) guidelines for PDAC strongly recommending molecular tumor analysis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular technologies continue to improve to overcome whatever challenges arise, with novel approaches showing promise in stratifying patient response to treatment in many tumor types [ 72 ]. As for pancreatic cancer, several groups have developed informatics designs that purport to identify and stratify patients into clinically actionable subtypes [ 74 ] accurately; these have yet to be assessed in clinical trials. Nonetheless, these numerous studies have shown the feasibility of incorporating molecular analysis into current clinical practice to screen patients and assign them to matched chemotherapy treatments, at least within the United States [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent identification of intrinsic transcriptomic subtypes of PDAC provides an alternative strategy for patient treatment selection–reviewed in depth by Xu Z et al (2021) . Transcriptomic profiling has identified 2 broad intrinsic PDAC classes, namely Classical and Basal-like with Basal-like tumours associated with significantly poorer outcomes and late-stage disease ( Moffitt et al, 2015 ; Collisson et al, 2019 ).…”
Section: Transcriptomics–identification Of Prognostic and Predictive Omic Subtypes Using Bulk And Lcm-derived Patient Materialsmentioning
confidence: 99%